(untitled) (Journal of the College of Basic Education, 2026)
This study examines the television coverage of Iraqi tourism on Iraqi satellite channels, focusing on the "Dinar" program on Al-Iraqiya Channel as an analytical model. The research highlights the central problem of imbalance and lack of comprehensiveness in presenting the diverse tourist attractions Iraq is endowed with, which include religious, archaeological, natural, and cultural tourism. The findings revealed a significant focus on the religious aspect of holy sites in Karbala and Najaf, alongside a clear neglect of other forms of tourism, despite the immense potential possessed by numerous regions such as Mosul and the southern marshes. Furthermore, the study uncovered a dominance of a negative tone in the media narrative, which emphasizes security and service challenges at the expense of opportunities and potentials. This is compounded by the hegemony of official governmental sources in shaping the media discourse, contrasted with an almost complete absence of local and community voices that could enrich the content and provide a more balanced perspective. Based on these results, the need arises for developing a more balanced tourism media policy that reflects Iraq’s geographical and cultural diversity, promotes positive and promotional aspects, and engages all stakeholders in the tourism sector to present a comprehensive and attractive image of Iraqi tourism. The theoretical framework of the study focused on tourism media, which is highly significant in the modern era due to increased global attention to it as a fundamental element shaping the structure and fabric of society. Consequently, this study was conducted to evaluate the direction of tourism media in Iraq and its impact on the domestic tourism industry. Primarily directed at researchers in the field of tourism media, this study aims to provide documented information and statistics on the development of this industry and its important national economic contribution.